2001
DOI: 10.1007/s00210-001-0499-5
|View full text |Cite
|
Sign up to set email alerts
|

The β2 subunit of nitric oxide-sensitive guanylyl cyclase is developmentally regulated in rat kidney

Abstract: We have recently shown that nitric oxide activates the beta2 subunit of soluble guanylyl cyclase. In the present study, we show developmental regulation of this subunit. Analysis of mRNA expression by RT-PCR and RNase protection analysis in kidneys revealed no expression of the beta2 subunit in neonatal and strong expression in adult rats. A reciprocal regulation with much lower expression levels was observed in rat lung. Further examination of kidneys from 3, 6, 16, 22, 25, 31 and 36-day-old rats showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…One previous study [23], focused on the aorta of 12-week-old HS offspring, showed that expression of sGC β1 was reduced while sGC β2 did not change. sGC β2 was reported to be richly expressed in the kidney [27,28]. Our results suggested that the reduction of sGC β1 and sGC β2 in the HS interlobar arteries could be the cause for the reduced ΔpD 2 in the HS offspring.…”
Section: Discussionmentioning
confidence: 51%
“…One previous study [23], focused on the aorta of 12-week-old HS offspring, showed that expression of sGC β1 was reduced while sGC β2 did not change. sGC β2 was reported to be richly expressed in the kidney [27,28]. Our results suggested that the reduction of sGC β1 and sGC β2 in the HS interlobar arteries could be the cause for the reduced ΔpD 2 in the HS offspring.…”
Section: Discussionmentioning
confidence: 51%
“…In the rat heart and kidney, sGC increased postnatally (7,9). In contrast, sGC expression in carotid and cerebral arteries was higher in 3-to 7-day-old lambs compared with adult sheep (37).…”
mentioning
confidence: 81%
“…The sGC a1 subunit is the most abundant a subunit in adult human tissues, including cardiovascular tissues 23 . Analysis of the tissue distribution of the b2 subunit has been difficult, owing to low mRNA concentrations of this subunit compared with other sGC subunits 24 . The sGC b2 subunit in uterine tissue was the lowest of the three subunits of mRNA expressed in our investigation.…”
Section: Commentmentioning
confidence: 99%